Paradigm Change in Liver Transplantation Practice After the Implementation of the Liver‐Kidney Allocation Policy. Issue 11 (16th August 2021) - Nagai, Shunji; Suzuki, Yukiko; Kitajima, Toshihiro; Ivanics, Tommy; Shimada, Shingo; Kuno, Yasutaka; Shamaa, Mhd Tayseer; Yeddula, Sirisha; Samaniego, Milagros; Collins, Kelly; Rizzari, Michael; Yoshida, Atsushi; et al.
Abstract : The Organ Procurement and Transplantation Network (OPTN)/United Network for Organ Sharing (UNOS) policy regarding kidney allocation for liver transplantation (LT) patients was implemented in August 2017. This study evaluated the effects of the simultaneous liver‐kidney transplantation (SLKT) policy on outcomes in LT alone (LTA) patients with kidney dysfunction. We analyzed adult primary LTA patients with kidney dysfunction at listing (estimated glomerular filtration rate [eGFR] less than 30 mL/minute or dialysis requirement) between January 2015 and March 2019 using the OPTN/UNOS registry. Waitlist practice and kidney transplantation (KT) listing after LTA were compared between prepolicy and postpolicy groups. There were 3821 LTA listings with eGFR <30 mL/minute included. The daily number of listings on dialysis was significantly higher in Era 2 (postpolicy group) than Era 1 (prepolicy group) (1.21/day versus 0.95/day; P < 0.001). Of these LTA listings, 90‐day LT waitlist mortality, LTA probability, and 1‐year post‐LTA survival were similar between eras. LTA recipients in Era 2 had a higher probability for KT listing after LTA than those in Era 1 (6.2% versus 3.9%; odds ratio [OR], 3.30; P < 0.001), especially those on dialysis (8.4% versus 2.0%; OR, 4.38; P < 0.001). Under the safety net rule, there was a higher KT probability after LTA (26.7% and 53% at 6 months in Eras 1 and 2, respectively; P = 0.02). After the implementation of the policy, the number of LTA listings among patients on dialysis increased significantly. While their posttransplant survival did not change, KT listing after LTA increased. The safety net rule led to high KT probability and a low waitlist mortality rate in patients who were listed for KT after LTA. These results suggest that the policy successfully achieved the goals of providing appropriate opportunities of KT for LT patients, which did not compromise LTA waitlist or posttransplant outcomes in patients with kidney dysfunction and provided KT opportunities if patients developed kidney failure after LTA.